Analisis Tingkat Maturitas Sistem Pengendalian Intern Pemerintah (SPIP) - Shadiya Freya Rosaline; Hastuti; Ahmad Syarief (Indonesian Accounting Research Journal, 2021)
The purpose of this study is to assess the maturity level of the Government Internal Control System (SPIP) at the Bandung State Polytechnic (Bandung State Polytechnic). This research is descriptive with a qualitative approach. Assessment of SPIP implementation is carried out by testing the SPIP elements, namely the control environment, risk assessment, control activities, information and communication and internal control monitoring which refers to the Regulation of the Head of BPKP Number: S-354 / SATGAS PP SPIP / 2014 concerning Guidelines for Assessment of Maturity Level Implementation of SPIP in government agencies and PP 60 of 2008 on SPIP. The research population consisted of 37 structural officers at the Bandung State Polytechnic. However, of the 37 respondents who were targeted, only 26 respondent data could be collected, because at the time of data collection it was affected by the spread of the Covid 19 virus so that the process of distributing questionnaires and data collection was hampered. Because in that period it was still in the Work From Home (WFH) period so that it affected the number of returned questionnaires. From the results of the analysis it is known that the application of SPIP at the Bandung State Polytechnic is at level 2 or at the developing level.